Influence of Motivation to Natural Sciences Mental Retardation Students on Learning Outcomes in Schools Organize Inclusive Education - Tri Wiryanto (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2021)
A person's success in reaching a point in the learning process depends on oneself and the environment, a great desire is in line with the effort used, this desire is called motivation. The purpose of this study was to determine the effect of learning motivation in science for mentally retarded students on learning outcomes in schools providing inclusive education. This research technique uses quantitative research. The research subjects were teachers at the School of Inclusive Education in Surakarta City. The results of data processing and statistical testing obtained a significance value (Sig) of 0.031. Thus, the value of Sig. 0.031 < probability 0.05, thus H0 is rejected and H1 is accepted. It can be concluded that